Investigation of thermoelectric material based on Lu1-xZrxNiSb solid solution. I. Experimental results - Romaka, V.A.; Stadnyk, Yu.; Romaka, L.; Horyn А.; Pashkevich, V.; Nychyporuk, H.; Garanyuk, P. (Physics and Chemistry of Solid State, 2022)
The effect of doping of half-Heusler phase p-LuNiSb (MgAgAs structure type) by Zr atoms on the structural, kinetic, energetic and magnetic characteristics of the semiconductor solid solution Lu1-xZrxNiSb was studied in the ranges: T = 80–400 K, x = 0–0.10. From experimental studies it has been established that doping of p-LuNiSb compound with Zr atoms simultaneously generates both structural defects of acceptor and donor nature, the concentration of which increases with increasing content of Zr atoms. It was shown that the investigated semiconductor solid solution Lu1-xZrxNiSb is a promising thermoelectric material.